Exogenous Melatonin Confers Salt Stress Tolerance to Watermelon by Improving Photosynthesis and Redox Homeostasis - Li, Hao; Chang, Jingjing; Chen, Hejie; Wang, Zhongyuan; Gu, Xiurong; Wei, Chunhua; Zhang, Yong; Ma, Jianxiang; Yang, Jianqiang; Zhang, Xian (Frontiers in Plant Science, 2017)
Melatonin, a pleiotropic signal molecule, has been shown to play important roles in the regulation of plant growth, development and responses to environmental stresses. Since a few species have been investigated to unveil the effect of exogenous melatonin on salt stress, the underlying mechanism of melatonin-mediated salt stress tolerance in other plant species still remains largely unknown. In this study, the effects of melatonin on leaf photosynthesis and redox homeostasis in watermelon were examined under salt stress (300 mM NaCl) along with different doses of melatonin (50, 150, and 500 μM) pretreatment. NaCl stress inhibited photosynthesis and increased accumulation of reactive oxygen species (ROS) and membrane damage in leaves of watermelon seedlings. However, pretreatment with melatonin on roots alleviated NaCl-induced decrease in photosynthetic rate and oxidative stress in a dose-dependent manner. The protection of photosynthesis by melatonin was closely associated with the inhibition of stomatal closure and improved light energy absorption and electron transport in photosystem II, while the reduction of oxidative stress by melatonin was attributed to the improved redox homeostasis coupled with the enhanced activities of antioxidant enzymes. This study unraveled crucial role of melatonin in salt stress mitigation and thus can be implicated in the management of salinity in watermelon cultivation.